How negative accounting news events, voluntary ESG assurance, and assurance provider influence consumer purchasing intentions - Hampton, Clark; Knutson, Macy; Masli, Adi; Stefaniak, Chad (Accounting, Organizations and Society, 2025)
Consumers are increasingly conscientious of societal and environmental impacts of their purchases, prompting companies to make environmental, social, and governance (ESG) claims and engage in voluntary ESG assurance. However, prior literature lacks insight into whether consumers consider negative accounting news events (e.g., error/irregularity restatements) and their effects on purchasing intentions. Using real world consumers of sustainable goods, we investigate how varying levels of negative accounting news events (i.e., error or irregularity restatements), the presence of ESG product-quality assurance (e.g., cage free egg certification), and the type of assurance provider (e.g., an accounting firm that also audits the financial statements, an accounting firm that does not audit the financial statements, government agency) influence purchasing intentions and organizational legitimacy perceptions. We find that consumers surrogate negative accounting news events as indicators of ESG claim reliability, negatively impacting purchasing intentions, especially for more severe events (e.g., irregularity). However, ESG product-quality assurance partially mitigates these negative effects. Moreover, we find that when an error restatement occurs, the mitigating effect is less pronounced when the same firm provides both financial statement and ESG product-quality assurance compared to a governmental agency or non-financial statement auditor. Finally, when irregularities occur, though product-quality assurance partially mitigates the detrimental effects, there is no difference between assurance providers, likely because management's willingness to deceive auditors decreases the perceived reliability of assurance in general. Our results suggest boards should obtain ESG product-quality assurance and carefully select their assurance providers.